Three‐dimensional intravital imaging in bone research. Issue 12 (18th October 2019) - Liu, Yuhao; Yuan, Quan; Zhang, Shiwen
Abstract: Intravital imaging has emerged as a novel and efficient tool for visualization of in situ dynamics of cellular behaviors and cell‐microenvironment interactions in live animals, based on desirable microscopy techniques featuring high resolutions, deep imaging and low phototoxicity. Intravital imaging, especially based on multi‐photon microscopy, has been used in bone research for dynamics visualization of a variety of physiological and pathological events at the cellular level, such as bone remodeling, hematopoiesis, immune responses and cancer development, thus, providing guidance for elucidating novel cellular mechanisms in bone biology as well as guidance for new therapies. This review is aimed at interpreting development and advantages of intravital imaging in bone research, and related representative discoveries concerning bone matrices, vessels, and various cells types involved in bone physiologies and pathologies. Finally, current limitations, further refinement, and extended application of intravital imaging in bone research are concluded. Abstract : This review is aimed at interpreting development and advantages of intravital imaging as an emerging invaluable methodology, and summarizing related representative discoveries in bone physiologies and pathologies. It also indicates current limitations, further refinement and extended application of intravital imaging in bone research. If you are interested in both intravital imaging and bone biology, this review is hopefully your dish.